The Impact of Industrial Revolution 4.0 on the Creative Economy Sector in Indonesia: A Literature Review of Opportunities and Challenges - Efendi, Efendi (Majapahit Journal of Islamic Finance and Management, 2025)
The industrial revolution 4.0 has had a significant impact on the development of the creative economy sector in Indonesia, both in terms of opportunities and challenges. To maximize its benefits, collaborative efforts are needed between the government, industry players, and the community to overcome existing challenges and utilize technological opportunities to encourage sustainable growth in the creative economy sector. This research is a qualitative research type that uses a library research approach. Data collection was carried out through a literature study, which involved searching, selecting, and collecting various relevant documents or literature. The results of the study indicate that: 1). The impact of the industrial revolution 4.0 on the development of the creative economy sector in Indonesia is that the industrial revolution 4.0 encourages digital transformation in the Indonesian creative economy sector, expanding market access through digital platforms and enabling more innovative production. However, tighter competition and the need for technological adaptation pose challenges for creative industry players. 2). The opportunities of the industrial revolution 4.0 for the development of the creative economy sector in Indonesia are that the industrial revolution 4.0 opens up great opportunities for the Indonesian creative sector through technology-based innovation, collaboration between the creative sector and technology, and the creation of new jobs in the digital field. Digital platforms enable Indonesian creative products to penetrate the international market. 3). The challenges posed by the Fourth Industrial Revolution (I4.0) to the development of Indonesia's creative economy sector include limited digital infrastructure and skills, as well as intense global competition. Furthermore, copyright and intellectual property protection are also crucial issues that require attention for the creative economy sector to thrive.